ASME 2021 3rd International Offshore Wind Technical Conference 2021
DOI: 10.1115/iowtc2021-3545
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Capacity Factor of Weather-Routed Energy Ships Deployed in the Near-Shore

Abstract: The energy ship concept has been proposed as an alternative wind power conversion system to harvest offshore wind energy. Energy ships are ships propelled by the wind and which generate electricity by means of water turbines attached underneath their hull, The generated electricity is stored on-board (batteries, hydrogen, etc.) It has been shown that energy ships deployed far-offshore in the North Atlantic Ocean may achieve capacity factors over 80% using weather-routing. The present paper complements this res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study showed that ESs can achieve very high capacity factors when optimal routes are followed. A subsequent study showed that ESs may also be used to supply power to small, coastal communities, but that capacity factors may be significantly lower in near-shore operation (Abd Jamil et al, 2021). There is clearly a large scope for future work to optimize routing based on fuel production/offload, O& M, and wind/sea-state forecasts.…”
Section: Energy Shipsmentioning
confidence: 99%
“…This study showed that ESs can achieve very high capacity factors when optimal routes are followed. A subsequent study showed that ESs may also be used to supply power to small, coastal communities, but that capacity factors may be significantly lower in near-shore operation (Abd Jamil et al, 2021). There is clearly a large scope for future work to optimize routing based on fuel production/offload, O& M, and wind/sea-state forecasts.…”
Section: Energy Shipsmentioning
confidence: 99%